Thailand in the Cold War - Phillips, Matthew (Historian) (London : Routledge, 2017)
"Thailand's position during the Cold War was ambiguous: the country's political leadership was very keen to maintain the country's independence on the world stage, yet at the same time was anxious to establish the country's credentials as staunchly anti-communist. However, as this book argues, Thailand, though never formally a client state of the United States, was very closely embedded in the Western camp through the commitment of Thailand's cosmopolitan urban communities to developing a modern, consumerist lifestyle. Considering popular culture, including film, literature, fashion, tourism and attitudes towards Buddhism, the book shows how an ideology of consumerism and integration into a "free world" culture centred in the United States gradually took hold and became firmly established, and how this popular culture and ideology was fundamental in determining Thailand's international political alignment"--
"A theatre with two stages" : Jim Thompson's Thailand -- In and out of Vogue : dressing for progress before and after 1945 -- If not "great," then what? : rethinking Thainess in post-war Bangkok -- Cultural spectacle, political authority and the subversion of Thai modernity -- The Tourist Organisation of Thailand and Cold War propaganda -- It's a small world after all : Thailand's integration into free world culture.
Reprint. Originally published: 2016.
Keywords: Popular culture -- Thailand -- History -- 20th century; Cold War; Thailand -- Foreign relations -- United States; United States -- Foreign relations -- Thailand; Thailand -- Foreign relations -- 1945-1988.